Blended Learning Based on Heutagogy as a Determinant of Student Engagement in Islamic Education - Salsabila, Unik Hanifah; Sukiman, Sukiman; Sibawaihi, Sibawaihi (FKIP Universitas Lampung, 2022)
Blended Learning Based on Heutagogy as a Determinant of Student Engagement in Islamic Education. Objective: Blended learning by prioritizing a heutagogical approach in Islamic Education needs to be analyzed to determine the potential for successful student engagement. Methods: Therefore, this study classifies, regresses, and predicts the determinants of the interaction of 128 students in a literacy project using three indicator variables; discussions, presentations, and publications. Findings: This study found an f value of 85.79 +/- 5.83 (micro average: 86.27) with positive class completeness at an accuracy of 80.71% in classification analysis with a decision tree, f value 80.33% with an accuracy of 72.86%, and classification error of 27.14% in predictive analysis with Naïve Bayes, and the significance of t count 4.713 > t table 1.97912 in regression analysis with SPSS. Conclusion: This study concludes; that (1) discussion determines mastery in heutagogy learning, (2) discussion activities have a positive effect on understanding in heutagogy learning, and (3) discussion determines engagement in completing assignments. Keywords: blended learning, heutagogical, Islamic education, student engagement.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202230